The evaluation of speech of children with cochlear implants and hearing-aid users by trained and untrained listeners - Šindija, Branka (Array, 2002)
Recordings of the speech of children with cochlear implants and children with traditional hearing aids were presented to trained and untrained listeners (therapists and students, respectively). In spite of the differences between the two groups of judges, their evaluation scores with respect to voice quality and overall intelligibility were in agreement in the sense that the cochlear implanted children received consistently higher scores.